Women in Foreign Trade Policy: The case of Chile (1990-2022) - López Giral, Dorotea; Henríquez Uzal, María José (Latin American Journal of Trade Policy, 2023)
Despite the gradual incorporation of women in different spheres of Chilean public policy since 1990, there is not enough research on the different impacts of this. For this reason, this article aims to provide some preliminary conclusions on the number of women, barriers that they face and identified the main topics where they worked in trade negotiations, between 1990 and 2022. The research is oriented to analyze Chilean Free Trade Agreements and at the World Trade Organization, focusing on the Chilean negotiation teams. Some initial findings demonstrate that there has been an increase in the entry of women as negotiators, especially in topics such as trade in services; however few women were appointed as chief negotiators, reflecting a persistent gender gap in the workplace and in decision-making. The research is being carried out on the basis of specialized literature and interviews with qualified informants.